The psychology of academic achievements.[article]. - Winne,Phillip H.
Educational psychology has generated a prolific array of findings about factors that influence and correlate with academic achievement. We review select findings from this voluminous literature and identify two domains of psychology: heuristics that describe generic relations between instructional designs and learning, which we call the psychology of "the way things are" and findings about metacognition and self-regulated learning that demonstrate learners selectively apply and change their use of those heuristics, which we call the psychology of "the way learners make things." Distinguishing these domains highlights a need to marry two approaches to research methodology: the classical approach, which we describe as snapshot, bookend, between-group experimentation; and a microgenetic approach that traces proximal cause-effect bonds over time to validate theoretical accounts of how learning generates achievements. We argue for fusing these methods to advance a validated psychology of academic achievements